Assimilation of coconut coir pith in slow sand filter (SSF's) to improve water quality in water treatment plant - Nur Farezza, Jasmi (2010)
During this modern era, the majority of rural communities are still drinking superficial water that does not meet the required standard of quality, causing serious health problems. Filtration is one of the water treatment processes to ensure our drinking water is safe from physical contamination. Therefore, in the study was investigating the potential of slow sand filtration as a biofiltration by adding natural material (coconut coir pith) as a medium to filter raw water as to reduce turbidity, total suspended solid, heavy metal and presence of pathogen and feacal coliform and also to reduce chemical additive in the disinfection process which is harmful to the communities. The focus of this study is to investigate the effectiveness Slow. Sand Filtration in treating raw water sample taken from JBA at water treatment plant at Semambu. Ten parameters were analyzed which include pH, turbidity, Total Suspended Solids (TSS), Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Coliform (TC), Escherichia Coli (E. Coli), Iron (Fe), Cooper (Cu) and Cadmium (Cd). The purpose of this study is to compare the effluent of water sample after treatment with conventional slow sand filtration and with integrated slow sand filtration which has additional coconut coir pith of granular activated carbon (GAC) layer in between of the filter bed. During this study, two pilot models of filter drum is built and the material will be used are wash sand (0.15mm - 0.3mm), gravel sand (2mm-5mm) and coconut coir pith as GAC From the result obtained, all the parameters were analyzed comply with Malaysian Drinking Water Standard 2009 guidelines. From the study, all result is most under range/limit in Malaysian Standard 2009. From the both model analysis, we can conclude that the water are safe be drink based on the small and acceptable limit of presence of heavy metal and the most effective type of filtration is with adding activated carbon in the medium of slow sand filtration tank.